Delaying rewards has greater effect on altruism when the beneficiary is socially distant - Jerzy Osiński; Adam Karbowski (PLoS ONE, 2017)
Based on the assumption that social distance and time are dimensions of psychological distance important for altruistic choices it was predicted that enhancement of altruism due to delaying rewards when choosing between a reward for oneself and for another person would be more pronounced the greater the social distance between the subject and another person. In order to test this hypothesis, social discounting using hypothetical monetary rewards and manipulation of social distance and reward delay was measured in a group of 161 college students. The results indicate that delaying rewards increasingly enhances preference for altruistic choices as the social distance between subject and beneficiary grows.
Keywords: D01; D03; 330; altruism; discounting